Fostering Innovative Work Behavior Through Ethical Leadership and Organizational Culture: The Mediating Role of Job Satisfaction - Kusumawati, Dian; Wardoyo, Dewie Tri Wijayati; Witjaksono, Andre Dwijanto (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the effect of ethical leadership style and organizational culture on employees’ innovative work behavior, with job satisfaction as a mediating variable. The research is grounded in the growing need for moral leadership and a supportive work culture to enhance organizational competitiveness amid rapid environmental changes. A quantitative approach with a survey method was employed, involving 76 employees of the UPTD Jagir Community Health Center in Surabaya City. Data were analyzed using the Structural Equation Modeling (SEM) technique with the assistance of SmartPLS software. The findings reveal that both ethical leadership style and organizational culture have a significant positive effect on employees’ innovative work behavior. Furthermore, job satisfaction plays a significant mediating role in the relationship between ethical leadership style, organizational culture, and innovative work behavior. These results indicate that employees’ innovative behavior is not only shaped by ethical leadership and organizational culture but is also strongly influenced by their level of job satisfaction. The study provides practical implications for organizational management, emphasizing the importance of strengthening ethical values in leadership and cultivating a work culture that fosters creativity and job satisfaction.